Ethics of planning for, and responding to, pandemic influenza in Sub Saharan Africa: qualitative study - Sambala, Evanson Zondani (2014)
This thesis argues that ethical issues in Ghana and Malawi represent barriers to pandemic influenza management and prevention. The ways in which ethical issues arise and are manifested are poorly understood, in part because there is little knowledge and inadequate Planning for, and Response to, Pandemic Influenza (PRPI). Rather than offering simple answers, this thesis describes how ethical problems emerge in the course of pandemic authorities performing their everyday duties. The central aim is to understand what ethical issues mean to policymakers and how they may be resolved. An extensive review of the experiences of the 1918 influenza pandemic including the epidemiology is examined to illustrate the profound impact of the disease and lessons that can be learnt. The study operates at two distinct but related levels. Firstly there is an investigation of PRPI at a broad level. Secondly, an exploration of the ethical issues that emerges from PRPI within the analytical framework of decision-making models. A qualitative study using semi-structured interviews is used to conduct the study with a “purposive sampling” of forty six policymakers from Malawi (22) and Ghana (24).